Measuring and analyzing the correlations between the Iraq Stock Exchange index and commodity market indices for the period (2005-2023) (Entrepreneurship Journal for Finance and Business, 2024)
The research aims to measure and analyze the correlations between the returns of the Iraq Stock Exchange index (RISX) and the returns of commodity markets represented by the returns of the OPEC oil market (ROPEC), the returns of 21-carat gold market (RPG21), and the returns of the wheat market (RPW)), relying on monthly data for the period from January 1, 2005 to December 31, 2023, and using the Dynamic Conditional Correlation-GARCH (DCC-GARCH) model. To determine the extent of the impact of the returns of the Iraq Stock Exchange index and commodity market indicators on conditional volatilities, and whether there is a dynamic conditional relationship between these markets, the results showed negative relationships between the returns of ROPEC, RPW and the returns of the Iraq Stock Exchange index (RISX). This relationship may provide investors with an opportunity to diversify their portfolios and reduce overall risks. There are also positive relationships between the returns of commodity markets on one hand, and between the returns of the Iraq Stock Exchange index (RISX) and the returns of the gold market (RPG21) on the other hand. And these links indicate that the returns of all these markets tend to move in the same direction, which means that investors may not achieve diversification benefits by investing in all of these markets at the same time. Therefore, it is necessary to increase the openness of the Iraqi stock market and to seek to enhance its information technology and transparency in order to increase the capacity and smoothness of information flow to and from the market, giving local and foreign investors and brokers more ability to hedge and predict the expected correlations and fluctuations in those markets.